Are universities responding to the needs of students from refugee backgrounds? - Earnest, Jaya; Joyce, A.; de Mori, Gabriella; Silvagni, G. (Australian Council for Educational Research, 2010)
Although many Australian universities have been proactive in responding to students' diverse needs through orientation and support programs, very little is known about programs needed for the successful transition of students from refugee backgrounds into tertiary study. Facilitating the early engagement of students with their studies and campus life is linked to greater student satisfaction, improved retention rates and better educational outcomes. One of the challenges that academics face is the paucity of research on the learning styles and academic needs of African and Middle Eastern students from refugee backgrounds.This paper reports on a needs analysis undertaken with a group of students from refugee backgrounds in Victoria and Western Australia, using in-depth interviews and focus group discussions. Participants reported that current support systems and programs are inadequate or non-existent and that many feel disadvantaged compared to Australian-born and international students. The article concludes with recommendations on how universities can better respond to the needs of students from refugee backgrounds.